Molecular compartmentalization of lateral geniculate nucleus in the gray squirrel (Sciurus carolinensis) - Felch, Daniel L.; Van Hooser, Stephen D. (Frontiers in Neuroanatomy, 2012)
Previous research has suggested that the three physiologically defined relay cell-types in mammalian lateral geniculate nucleus (LGN)—called parvocellular (P), magnocellular (M), and koniocellular (K) cells in primates and X, Y, and W cells in other mammals—each express a unique combination of cell-type marker proteins. However, some of the relationships among physiological classification and protein expression found in primates, prosimians, and tree shrews do not apply to carnivores and murid rodents. It remains unknown whether these are exceptions to a common rule for all mammals, or whether these relationships vary over a wide range of species. To address this question, we examined protein expression in the gray squirrel (Sciurus carolinensis), a highly visual rodent. Unlike many rodents, squirrel LGN is well laminated, and the organization of X-like, Y-like, and W-like cells relative to the LGN layers has been characterized physiologically. We labeled tissue sections through visual thalamus with antibodies to calbindin and parvalbumin, the antibody Cat-301, and the lectin WFA. Calbindin expression was found in W-like cells in LGN layer 3, just adjacent to the optic tract. These results suggest that calbindin is a common marker for the konicellular pathway in mammals. However, while parvalbumin expression characterizes P and M cells in primates and X and Y cells in tree shrews, here it identifies only about half of the X-like cells in LGN layers 1 and 2. Putative Y/M cell markers did not differentiate relay cells in this animal. Together, these results suggest that protein expression patterns among LGN relay cell classes are variable across mammals.